Law Enforcement Against Khalwat Offenses Committed by Teenagers in Banda Aceh City: Penegakan Hukum Terhadap Pelanggaran Jarimah Khalwat oleh Remaja di Kota Banda Aceh - Muhajirin; Sulfanwandi; Roslaili, Yuni (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2025)
Banda Aceh is widely recognized as a region that formally implements Islamic law; however, violations of jarimah khalwat among adolescents continue to occur in social life. This situation reflects a paradox between the legal norms stipulated in Aceh Qanun Number 6 of 2014 on Jinayat Law and the actual behavior of adolescents in public and semi-private spaces. This study aims to analyze the phenomenon of jarimah khalwat violations committed by adolescents and to examine the enforcement of law against such violations in Banda Aceh. The research employs a qualitative approach using an empirical juridical method, with data collected through interviews with officers of the Civil Service Police Unit and Wilayatul Hisbah, field observations in vulnerable locations, and analysis of case data and applicable legal provisions. The findings indicate that law enforcement has been implemented through preventive measures, such as patrols and public outreach, as well as repressive actions including raids, guidance, and legal sanctions in accordance with the Jinayat Qanun. However, its effectiveness remains constrained by limited resources, low community participation, weak family roles, and strong social influences on adolescents. Therefore, effective enforcement requires synergy among the state, community, and family to foster legal awareness and ensure sustainable prevention.